Acoustic, aerodynamic, and vibrational effects of ventricular folds adduction in an ex vivo experiment - Zhixue Xiao; Jing Kang; Jinglin Su; Pingjiang Ge; Siyi Zhang (Laryngoscope Investigative Otolaryngology)
Abstract Objectives The excessive adduction of ventricular folds has been observed in patients with dysphonia and professional singers. Whether these changes in the ventricular folds are the cause or just a result of disease progression remains unclear, and their potential pathological and physiological implications are yet to be determined. This study aimed to examine the impact of different degrees of ventricular adduction on acoustics, aerodynamics, and vocal fold vibration. Methods The excised models of mild and severe ventricular adduction were established. We recorded the vibration pattern of vocal folds and ventricular folds and measured acoustic metrics, including fundamental frequency (F0), Jitter, Shimmer, harmonic‐to‐noise ratio (HNR), and sound pressure level (SPL). Furthermore, we evaluated the aerodynamics index through phonation threshold pressure (PTP), phonation instability pressure (PIP), mean flow rate (MFR), phonation threshold flow (PTF), and phonation instability flow (PIF). Results Irregular vibrations of the ventricular fold were observed during ventricular adduction. Notably, mild and severe ventricular adduction conditions showed a significant increase in PTP, Shimmer, and Jitter, whereas MFR, PIF, and HNR decreased compared with the control condition. Conclusions Ventricular adduction leads to the deterioration of acoustic and aerodynamic parameters. The aperiodic and irregular vibration of the ventricular folds may be responsible for this phenomenon, although further experiments are warranted. Understanding the functioning of ventricular folds can be beneficial in directing the treatment of muscle tension dysphonia and improving voice training techniques. Level of evidence: level 4.